Functional Chemical Properties And Antioxidant Capacity In Cocoa Paste After Vacuum Roasting Of Cocoa Beans - H., Rivera; P., Peláez; N, Martínez; M., Ureña (Migration Letters, 2024)
Cocoa beans roasting at a high temperature affect the content of functional compounds and the antioxidant capacity of the cocoa paste or liquor to be obtained. These products are the basis for the production of chocolates. The properties favorable to health in this product are affected. The objective was to evaluate the influence of vacuum roasting on the functional chemical properties and antioxidant capacity of cocoa paste. There were thirteen treatments and one control. The variables were roasting temperature and pressure (normal pressure and vacuum atmosphere). The results showed the influence of vacuum roasting of cocoa beans on the functional chemical properties and antioxidant capacity of pastes. The temperatures of 90°C, and 100°C, and the pressure of vacuum of 0.4 bar less affected the antioxidant capacities expressed as IC50 values ​​with DPPH and ABTS radicals, treatment T13 (100°C and 0.4 bar) produced activities of 84.88 ± 0.87 ug/mL and 48.19 ± 0.34 ug/mL, respectively. The optimization analysis of the roasting process presented 13 optimal solutions, highlighting the treatment at 90 °C and 0.8 bar for its greater desirability 0.816. The contents of phenols, flavonoids, and anthocyanins influenced the antioxidant capacity of cocoa pastes. The component analysis (PCA), PC1, and PC2 explained this direct correlation in 99%, highlighting the influence of phenols, flavonoids, and anthocyanins. Future research on vacuum roasting should determine what happens to specific compounds such as theobromine, catechins, and other phenols.